Hybrid Modification of Wheat Bran Using Microbial Processing and Ultrasound: Enhancements in Bran Composition and Bread Quality - Sik, Esra; Bekiroglu, Hatice; Icyer, Necattin Cihat; Ozulku, Gorkem (Mdpi, 2025)
This study investigates the effects of microbial bioprocessing (MB), ultrasound treatment (UT), and their combined application (hybrid method, HM) on the functional and nutritional enhancement of wheat bran (WB) and its impact on bread quality. MB was performed by using Saccharomyces cerevisiae with Levilactobacillus brevis LABE 32 (MB32) and Lactiplantibacillus plantarum LABE 29 (MB29). MB32 significantly increased soluble dietary fiber (SDF) and reduced phytic acid content by up to 25.7% when compared to the control. UT further decreased phytic acid content by 52.2% and enhanced phenolic compound release, contributing to improved antioxidant activity. The hybrid method (HM) demonstrated the strongest effect, reducing phytic acid content by 95% and enhancing antioxidant properties, including a 2.4-fold increase in bound antioxidant activity (bound-AA). Bread produced from modified WB showed improvements in specific volume (SV), texture, and nutritional composition. The HM-treated WB yielded bread with the highest SV, approximately 10% greater than the control, while MB29 produced significantly harder bread than other samples (p < 0.05). The HM-treated bread had the highest crust L* value and softest texture (p < 0.05). Nutritionally, only UT and HM treatments significantly increased the total dietary fiber (TDF) content, with the most pronounced increase observed in the HM treatment. Phytic acid degradation in the WB modified with MB32 and UT was in accordance with their breads, notably lowering phytic acid content. Additionally, MB32 and HM increased total phenolic content (TPC) and antioxidant activity, enhancing the bread's overall nutritional quality. In conclusion, the hybrid application of MB and UT (HM) proved to be the most effective in improving the functional and nutritional properties of WB and the resulting bread, including increased dietary fiber content, reduced phytic acid levels, and enhanced antioxidant activity.
Keywords: wheat bran modification; optimization; bread characteristics; nutritional properties